Pencemaran Dalam Pengelolaan Kebun Raya Universitas Mulawarman Samarinda Menurut Peraturan Pemerintah Nomor 63 Tahun 2002 Tentang Hutan Kota - Fakultas Hukum Universitas Mulawarman (Jurnal Beraja Niti, 2012)
Self-Supporting KSU Putra Mahakam ( PUMMA) doing contamination of great garden environment University of Mulawarman Samarinda do not indemnify and cure of management and environment done by Body Organizer of the great garden to great garden University of Mulawarman Samarinda, only limited to embroidering and fertilization and also cultivation. Contamination that happened in great garden University of Mulawarman Samarinda done by side of KSU Self-Supporting Putra Mahakam ( PUMMA) have resulted fish had by Body side Organizer Of Great Garden University of Mulawarman Samarinda and Body employees Organizer of great garden University of Mulawarman Samarinda residing in dead pool. In the case of this contamination is required by role and also Government of Town of Samarinda better again so that contamination of environment in great garden University of Mulawarman Samarinda do not recurred again. And if matter contamination of environment happened again Governmental side Town of Samarinda have to behave coherent to applying of applicable law sanction.